Analysis of Students’ Ability to Accept M-Learning Technology: An Exploratory Study from High Schools in Vietnam - Trinh, Le Thi Tuyet; Thao, Trinh Thi Phuong; Hang, Thu Thi Nguyen; Thanh, Nguyen Chi; Trung, Tran (International Journal of Interactive Mobile Technologies (iJIM), 2021)
With the availability of mobile devices capable of accessing the Internet in the Industry 4.0 era, M-learning methodology has been established. Based on the Technology Acceptance Model on technology adoption, this article analyses factors affecting the decision to use M-learning in Vietnam. The study used survey questionnaires with 238 students. The analysis shows to encourage students to choose to use M-learning is that educators need to pay attention to the design of appropriate courses to save time, improve learning efficiency, increase the mobility of learners and necessary introduce the convenience of courses to learners through many different channels.